Perancangan Sistem Evaluasi Kinerja Karyawan Berbasis Kompetensi (Studi Kasus Di PT. Pelindo Nusra) - Juliana, Mia; Kirana, Alicia (JURNAL RISET DAN APLIKASI TEKNIK INDUSTRI, 2025)
This journal discusses the competency-based employee performance evaluation. Objectivity is to enhance the competency-based employee performance evaluation system, in supporting the company's goals. The issue is the lack of efficiency and accuracy in the current manual performance evaluation system. This system is deemed inadequate in providing an accurate depiction of employee performance, thereby hindering development and motivation efforts. The proposed solution in this research is to integrate the performance evaluation system with the digital platform Portaverse. This step is expected to improve the efficiency and accuracy of evaluations, while also simplifying the process of collecting and analyzing employee performance data and the evaluation process more transparent and objective. With a better evaluation system, employees will be more motivated to develop and contribute optimally. Competency-based performance evaluation is seen as more relevant compared to traditional methods, as it better reflects employees' skills and potential.